Managing Recruitment, Selection and Induction Pr ocesses for T ertiary Institutions' Staff Positions in Nigeria. - OPARINDE, Olayiwola Raheef; BAMIRE, Felicia Bosede (International Journal of Educational Management, 2021)
This study looked into the recruitment, selection and induction process for tertiary institutions' staff position in Nigeria. Recruitment and selection processes are considered useful in every organization, because they help in finding the most suitable candidates for the jobs. In human resource management, recruitment and selection are important operations designed to make best use of employee strength so as to achieve the organizational goals. This is an opinion paper and hence, secondary data and on the point assessment of information were made use of. It was discovered that the recruitment and selection process in Nigerian tertiary institutions has often been subjective as a result of not attracting a large pool of qualified applicants. This was discovered to be due to bribery and corruption, tribalism, nepotism, recruitment of personnel based on quota system and many other factors that have characterised the public service in the country. The study, therefore, examined issues bordering on employment practices and placement, importance of developing recruitment, selection and induction policies and procedures, principles of recruitment and selection, factors affecting recruitment and selection, legal aspects in recruitment and selection, the importance of induction program and risks arising from ineffective induction among others. The authors concluded that due procedure should be followed when considering recruitment in the establishment to achieve the objectives of the organization and reduce staff turn-over and complaints to the barest minimum. Among the recommendations made are that establishments should guide against job discrimination and give equal rights and recognitions to all workers not minding their colour, language, religion, tribe or sex.